AN ANALYSIS OF JUNIOR HIGH STUDENT’S SCIENCE PROCESS SKILLS AFTER COVID-19 - Tri Lestari (Widya Mandala Surabaya Catholic University, 2023)
This research aims to analyze the science process skills of junior high school students after 2 years of distance learning or post-COVID-19. The research method used is a descriptive quantitative method using multiple choice questions with 30 items and 4 answer options with 5 SPS indicators: operationalizing definitions, designing experiments, identifying and controlling variables, formulating hypotheses, and describing and interpreting data. The SPS instrument was given to 28 private junior high school students in Surabaya, 9th grade. The results obtained were that the indicator of operationalizing definitions was 33.40% with a low category, designing experiments was 38.89% with a low category, identifying and controlling variables was 40.00% with a low category, formulating hypotheses was 33.00% with a low category, and describing and interpreting data was 44.00% with a low category. The questions 2 and 4 with the indicators of recognizing and controlling variables and articulating hypotheses yielded the fewest correct answers from the students. On question 25, students with the indicator of detecting and controlling variables received the majority of the right responses.